Serum hypoxia-inducible factor 1 alpha levels as a prognostic factor in acute ischemic stroke (Annals of Medical Research, 2023)
Aim: In order to survive, human cells must adapt to changes in the oxygen level of their environment. Many endogenous mechanisms operate in hypoxia. Hypoxia-inducible factor 1 (HIF-1) is a transcriptional protein involved in the head of the cascade that regulates the response of brain and other tissues to hypoxia. HIF-1 alpha (HIF-1α) is the main molecule that responds to hypoxia and is an important marker of cerebral hypoperfusion.Materials and Methods: Thirty-nine acute stroke patients aged between 18-80 years and 38 control patients included in our study. We aimed to examine the serum HIF-1α levels in early period of acute ischemic stroke. We also aimed to evaluate its usefulness in determining tissue damage due to hypoxia and the prognosis of the disease.Results: Serum HIF-1α levels were higher in acute ischemic stroke patients compared to the control group (p= 0.000). There was no significant correlation between infarct volumes, NHISS scores, blood pressure and HIF-1α values ​​of the stroke patients.Conclusion: HIF-1α could be an important biomarker in detecting cerebral hypoxia. It is possible to study this in human peripheral blood. Its usability in stroke may become widespread with studies on its therapeutic target.
Keywords: Hypoxia-inducible factor; HIF; HIF-1α; Ischemic stroke; Cerebral hypoperfusion